Molecular targets of Candida tropicalis biofilm adhesion proteins for Humulus lupulus and Artemisia absinthium essential oils - Chernei, Iryna S.; Dzichenka, Yaraslau U.; Cheshchevik, Vitali T. (Experimental Biology and Biotechnology, 2025)
Molecular docking was employed to identify potential molecular targets of Candida tropicalis biofilm adhesion proteins interacting with essential oil components from Humulus lupulus and Artemisia absinthium. The following components exhibited the highest affinity for C. tropicalis biofilm adhesion proteins: myrcene, linalool, humulene oxide, 4-decenoic acid, isoamyl butyrate, methyl-6-heptenoate, 2-nonanone, methyl isooctanoate, methyl octanoate, methyl nonanoate, geranyl isobutyrate (H. lupulus), as well as α- and β-thujone, sabinene, 2,4-thujadiene, geranyl propionate, terpinene-4-ol, trans-sobrerol, geranyl formate (A. absinthium). The identified compounds demonstrated interaction types with biofilm adhesion proteins similar to those of fluconazole but differed in the involvement of various key amino acid residues specific to each protein. Comparison of physico-chemical parameters and ADME properties of these compounds with those of fluconazole suggests their potential as a basis for developing novel antifungal agents with antibiofilm activity against C. tropicalis.
Keywords: adhesion proteins; biofilm; Candida; essential oil; Humulus lupulus; Artemisia absinthium; molecular docking; ADME properties